Notes on the ecology of Crypcoryne ciliata (Roxb.) School (Araceae) - Kartini Saibeh; Mashhor Mansor (1995)
According to Jacobsen (1987), Cryptocoryne ciliate (Roxb.) Schott, an aquatic member of the Araceae, is widely distributed in mangrove ecosystems in peninsular Malaysia. A study of its distribution within part of Larut Matang mangrove forest reserve, Perak, was carried out in ApriI 1994. The three main rivers in the area, Sungai Larut, Sungai Lang and Sungai Jebong were surveyed by sampan over a distance of 20 km.